Soluble Uric Acid Promotes Atherosclerosis via AMPK (AMP-Activated Protein Kinase)-Mediated Inflammation. Issue 3 (March 2020) - Kimura, Yoshitaka; Yanagida, Tamiko; Onda, Akiko; Tsukui, Daisuke; Hosoyamada, Makoto; Kono, Hajime
Abstract : Objective: Uric acid is supposed but not yet determined to be associated with atherosclerosis. Uric acid is released from damaged cells to form urate crystal, which is recognized by the immune system to produce IL (interleukin)-1. Danger signals and IL-1 have been shown to play an important role in atherosclerosis. We determined whether the physiological level of soluble uric acid promotes inflammation and develops atherosclerosis. Approach and Results: The secretion of IL-1β from human peripheral blood mononuclear cells mediated by NLRP3 (NACHT, LRR, and PYD domain-containing protein 3) inflammasome was promoted by physiological levels in serum uric acid. This augmentation of inflammation was mediated by the regulation of the AMPK (AMP-activated protein kinase)-mTOR (mammalian target of rapamycin) mitochondrial reactive oxygen species and HIF-1α (hypoxia-inducible factor-1α) pathway. In both of uricase transgenic and xanthine oxidase inhibitor–treated mice, decreased levels of uric acid resulted in the activation of AMPK and attenuation of the development of atherosclerotic plaques. Further, acute uric acid reduction by the administration of benzbromarone in healthy humans for 2 weeks significantly decreased plasma IL-18—an inflammasome-dependent cytokine. Conclusions: The data indicate that the development of atherosclerosis and inflammation is promoted by uric acid in vivo. Moreover, the lowering of uric acid levels attenuated inflammation via the activation of the AMPK pathway. This study provides mechanistic evidence of uric acid–lowering therapies for atherosclerosis. Abstract : Supplemental Digital Content is available in the text.